Main directions in development of organic industry in Ukraine and experience of innovation implementation: a comprehensive analysis - Калініченко, Антоніна Володимирівна; Мінькова, Ольга Григорівна; Сакало, Віктор Миколайович (Technology audit and production reserves, 2015)
Active development of organic agriculture sector is one of strategic priorities for Ukraine. That is why the study of effective ways and directions of development of organic farming is currently a relevant scientific task. In our study we present the results of the analysis of main driving forces and existing barriers for development of organic sector of agriculture in Ukraine. Based on obtained results, we are able to conclude that: • rich natural resource potential of Ukraine and a long tradition of natural farming provide the necessary preconditions for the effective development of organic production; • the main obstacle for development of the industry is the lack of financial commitment from the government; • the active forms of support for organic production currently include attracting of foreign and donor investments, as well as participation in international scientific and practical projects. We also present a comprehensive systematization of perspective directions for development of organic production in the form of structural and logic scheme. The main emphasis is on systemic, institutional, informational and organizational elements. In addition, the particular importance of regional and global markets, as well as the control of environmental safety is indicated. Most of these measures require complex research and development of the appropriate strategies and algorithms for their implementation. Therefore, our research is focused on the development of effective measures of regional support for organic farming. To a large extent the efforts are focused on Poltava region, which has considerable natural potential, long-established traditions of organic farming, as well as an attractive investment climate for foreign and domestic innovations.